Polri Return to Main Duty: Police Reconstruction Perspective after the "Duren Tiga" Incident - Pribadi, Slamet (Journal of Social Research, 2023)
In July 2022, a disturbing incident occurred in Duren Tiga, South Jakarta, where the majority of the suspects, victims, and witnesses were members of the National Police. The alleged premeditated murder took place at the Duren Tiga Police Service House. As a former police officer, this tragic event is deeply saddening and heart-wrenching. One can only hope that such incidents never happen again to anyone, regardless of their affiliation. However, amidst this sorrow, it serves as a critical turning point for reevaluating the overall development of the Indonesian National Police (Polri) organization. Despite continuous organizational development across generations, recent events, like the Duren Tiga Incident, have cast a shadow on the achievements of the police force. Witnessing this decline is disheartening. To chart a new course, Polri must revisit its core duties and functions. While organizational development has been ongoing, recent events have captured public attention, potentially undermining these efforts. Therefore, a renewed focus on the main functions and tasks is essential. This entails precise strategic planning encompassing legal politics, policy, and implementation. By refocusing on its core mission, Polri can rebuild trust and ensure that such tragic incidents remain a thing of the past. That way, the National Police should look back and focus on the main functions and tasks, which is one of the most accurate strategic plans, both in terms of legal politics, legal policy, and legal implementation.